Study of centrifugal atomisation mechanisms based on a simulated experiment - Evgeny Yu. Zhukov; Alibek S. Naurzalinov; Igor N. Pashkov (Frontier Materials & Technologies)
The process of melt dispersion on a rotating bowl is a common method for producing metal powders. It is difficult to study the dispersion process on real melts, including by visualisation methods. Therefore, it is proposed to study the influence of such factors as the jet fall height, liquid flow rate, surface wetting, and the presence of a bowl wall on the process of obtaining small droplets using a model liquid without crystallisation, recording the process by high-speed shooting. The purpose of this work is to determine the most favourable dispersion conditions, when all the supplied liquid turns into droplets without the formation of large droplets, additional jets leading to secondary spraying. A glycerol solution in water with a viscosity equal to the viscosity of tin melt was chosen as a model liquid. The dispersion process was shot on a high-speed camera with a shooting frequency of 1,200 frames per second. It was found that when increasing the melt flow, a change in the spray mode is observed. With an increase in pressure, the flow and kinetic interaction of the jet with the surface of the bowl, increase, and consequently, the excess liquid, which is sprayed prematurely, increases. At any flow of the supplied liquid, if the liquid does not get to the centre, secondary spraying occurs due to the destruction of the film, on the hydraulic jump, because of the uneven radial velocity at the peak of the jump. When the feed height changes from 100 to 150 mm, secondary spraying in the form of droplets is observed at the hydraulic jump area. The number of spirals and secondary spraying affect the increase in the size of the particle fraction. In the range of the jet fall height from 50 to 100 mm, an optimal process is observed, in which it is possible to obtain the smallest fraction. In the experiment, a tendency to improve the spraying process when increasing the bowl surface finish was observed. Due to the walls of the bowl, the path of the liquid before it leaves the bowl increases, drops flying above the surface of the bowl are destroyed into a film, therefore, the dispersion process improves.